Representing red and blue how the culture wars change the way citizens speak and politicians listen - Barker, David C. (David Christopher), 1969-; Carman, Christopher J. (New York ; Oxford : Oxford University Press, 2012)
This study presents an in-depth analysis of several years (conducted between 2004 and 2009) of national surveys designed specifically to assess public preferences for, and evaluations of, political representation in the US. In addition, unique aggregate data are used to examine how public preferences for representation influence how elected officials represent their constituents.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Party affiliation -- United States; Voting -- United States; Social choice -- United States; Political socialization -- United States; Politics and culture -- United States; Constituent power -- United States; Representative government and representation -- United States